C-Myc and viral cofactor Kaposin B co-operate to elicit angiogenesis through modulating miRNome traits of endothelial cells. Issue 1 (January 2016) - Chang, Hsin-Chuan; Hsieh, Tsung-Han; Lee, Yi-Wei; Tsai, Cheng-Fong; Tsai, Ya-Ni; Cheng, Cheng-Chung; Wang, Hsei-Wei
Abstract Background MicroRNAs (miRNAs) have emerged as master regulators of angiogenesis and other cancer-related events. Discovering new angiogenesis-regulating microRNAs (angiomiRs) will eventually help in developing new therapeutic strategies for tumor angiogenesis and cardiovascular diseases. Kaposi's sarcoma (KS), which is induced by the etiological infectious agent KS-associated herpesvirus (KSHV), is a peculiar neoplasm that expresses both blood and lymphatic endothelial markers and possesses extensive neovasculature. Using KSHV and its proteins as baits will be an efficient way to discover new angiomiRs in endothelial cells. Kaposin B is one of the latent viral genes and is expressed in all KSHV tumor cells. Since Kaposin B is a nuclear protein with no DNA-binding domain, it may regulate gene expression by incorporating itself into a transcription complex. Results We demonstrated that c-Myc and Kaposin B form a transcription complex and bind to the miR-221/-222 promoter, thereby affecting their expression and anti-angiogenic ability. By small RNA sequencing (smRNA-Seq), we revealed that 72.1 % (173/240) of Kaposin B up-regulated and 46.5 % (113/243) of Kaposin B down-regulated known miRNAs were regulated by c-Myc. We also found that 77 novel miRNA were up-regulated and 28 novel miRNAs were down-regulated in cells expressing both c-Myc and Kaposin B compared with cells expressing Kaposin B only. The result was confirmed by RNA-IP-seq data. Conclusions Our study identifies known and novel c-Myc-regulated microRNAs and reveals that a c-Myc-oriented program is coordinated by Kaposin B in KSHV-infected cells.